Some sum reciprocal

Level pending

Let f f be a function such that

f ( x ) = k = 0 k + 1 x k f(x)=\displaystyle \sum_{k=0}^\infty {\frac {k+1}{x^k}}

If f ( 161 ) = S f(-161)=S , what value of x x satisfies f ( x ) = 1 S f(x) = \frac{1}{S} ?


The answer is 162.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ryan Phua
Dec 18, 2013

Note that:

f ( x ) = k = 0 k + 1 x k = 1 + 2 ( 1 x ) + 3 ( 1 x ) 2 + 4 ( 1 x ) 3 f(x) = \displaystyle \sum_{k=0}^\infty \frac {k+1}{x^k} = 1+2(\frac{1}{x})+3(\frac{1}{x})^2+4(\frac{1}{x})^3 \dots

x f ( x ) = x + 2 + 3 ( 1 x ) + 4 ( 1 x ) 2 + 5 ( 1 x ) 3 x{f(x)} = x+2+3(\frac{1}{x})+4(\frac{1}{x})^2+5(\frac{1}{x})^3 \dots

x f ( x ) f ( x ) = x + 1 + 1 x + ( 1 x ) 2 + ( 1 x ) 3 x{f(x)}-f(x)=x+1+\frac{1}{x}+(\frac{1}{x})^2+(\frac{1}{x})^3 \dots

( x 1 ) f ( x ) = x + k = 0 ( 1 x ) k = x + 1 1 1 x = x + x x 1 = x 2 x 1 (x-1){f(x)} = x + \displaystyle \sum_{k=0}^\infty (\frac{1}{x})^k = x+\frac{1}{1-\frac{1}{x}} = x+\frac{x}{x-1} = \frac{x^2}{x-1}

Therefore, f ( x ) = x 2 x 1 x 1 = x 2 ( x 1 ) 2 f(x) = \frac{\frac{x^2}{x-1}}{x-1} = \frac{x^2}{(x-1)^2}

So, f ( 161 ) = ( 161 ) 2 ( 161 1 ) 2 = 161 2 162 2 = S f(-161) = \frac{(-161)^2}{(-161-1)^2} = \frac {{161}^2}{{162}^2} = S

f ( x ) = 1 S = 162 2 161 2 = x 2 ( x 1 ) 2 x = 162 f(x) = \frac{1}{S} = \frac {{162}^2}{{161}^2} = \frac{x^2}{(x-1)^2} \Rightarrow x=\boxed {162}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...